2015
DOI: 10.1111/1462-2920.12587
|View full text |Cite
|
Sign up to set email alerts
|

Microbial community of the deep‐sea brine Lake Kryos seawater–brine interface is active below the chaotropicity limit of life as revealed by recovery of mRNA

Abstract: Microbial community of the deep-sea brine Lake Kryos seawater-brine interface is active below the chaotropicity limit of life as revealed by recovery of mRNA Yakimov, M. M., La Cono, V., Spada, G. L., Bortoluzzi, G., Messina, E., Smedile, F., ... Giuliano, L. (2015). Microbial community of the deep-sea brine Lake Kryos seawater-brine interface is active below the chaotropicity limit of life as revealed by recovery of mRNA. Environmental Microbiology, 17 (2) This is the accepted version of the following article… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
141
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(146 citation statements)
references
References 83 publications
5
141
0
Order By: Relevance
“…An increasing body of evidence suggests that it is frequently the net effect of diverse stress parameters that defines the boundary space for life (8,(13)(14)(15)(16)(17)(18). The sea ice bacterium Shewanella gelidimarina, for example, has been shown to exhibit an increased temperature range for cell division when cultured at high (NaCl) salinity, with increases in membrane lipid packing and fatty acid content conferring tolerance of both conditions (13).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…An increasing body of evidence suggests that it is frequently the net effect of diverse stress parameters that defines the boundary space for life (8,(13)(14)(15)(16)(17)(18). The sea ice bacterium Shewanella gelidimarina, for example, has been shown to exhibit an increased temperature range for cell division when cultured at high (NaCl) salinity, with increases in membrane lipid packing and fatty acid content conferring tolerance of both conditions (13).…”
mentioning
confidence: 99%
“…Despite our knowledge of the physicochemical boundaries for microbial cell division having been greatly advanced over the past three decades, we are only beginning to understand how interactions between different stressors define biological permissiveness for natural ecosystems (8,(13)(14)(15)(16)(17)(18). In particular, while several studies have identified minimal and maximal limits for microbial life in response to the surrounding environment (1,5,(19)(20)(21), there is a paucity of information on how rates of cell division are impacted by multiple stress parameters within extreme habitats.…”
mentioning
confidence: 99%
“…high cytosolic accumulation of these additives [86]. In this regard, the interactions between macromolecules and ions or ion-clusters are relevant toward defining the geochemical boundary conditions for life and predicting planetary habitability [69,87]. Such investigations indicate the non-additive nature of net chaotropic and kosmotrophic effects of solution mixtures of diverse salts and organic molecules.…”
Section: Discussionmentioning
confidence: 99%
“…Trehalose, sorbitol, ectoine, mannitol, and betaine induce increases in the pre-nucleation slope in comparison to the relative reference experiments at both pH values. At pH 9.0, this corresponds to percentage increases of about 87,44,29,26, and 20%, respectively. At higher pH (9.75), these effects are more pronounced, leading to corresponding increases of about 41,56,66,109, and 39% in the pre-nucleation slope.…”
Section: On Kosmotropes and Chaotropesmentioning
confidence: 92%
“…The Discovery brine, the most extreme in this regard, contains about 16 times the amount of MgCl 2 of the Lake Vanda brine. However, the deep Mediterranean brines are nearly devoid of CaCl 2 , and most have high levels (3 to 4 M) of NaCl; hence, the chaotropic effects of MgCl 2 are offset somewhat by the kosmotropic effects of NaCl (47,50). Notably, however, the Discovery brine is an exception in this regard, as it contains low levels of NaCl; in terms of chaotropicity and water potential, the characteristics of this highly unusual brine are probably at or very near the limits of those that can support life (45)(46)(47)(48)(49)(50).…”
Section: Discussionmentioning
confidence: 99%